Molecular Docking-Based Insights Into The Antifungal Potential Of Turmerone: Mechanistic Evaluation Of Fungal Enzyme Inhibition - Anoosha, Anoosha; Prabhu K, Prabhu K; CS, Janaki; Kavimani, Kavimani; M, Shresht; Annand, Suhani (Journal of Neonatal Surgery, 2025)
Fungal infections continue to be a major global health threat, necessitating the development of new therapeutic strategies. Turmerone (PubChem ID: 160512), a bioactive compound, has shown promise in several biological activities, yet its antifungal potential remains underexplored. In this study, we evaluated the antifungal activity of Turmerone through molecular docking simulations against three key fungal enzymes: beta-glucocerebrosidase (PDB ID: 9FA3), Demethylase (PDB ID: 6UEZ), and Upc2 (PDB ID: 7VPU), all of which are crucial for fungal cell wall synthesis and metabolism. The docking results revealed that Turmerone exhibited the strongest binding affinity with beta-glucocerebrosidase, with a binding energy of -7.87 kcal/mol (Ki = 1.71 µM). This interaction was facilitated by the formation of hydrogen bonds with the residues LYS-464 and PRO-67, suggesting a stable binding mechanism. For Demethylase, Turmerone demonstrated a binding energy of -6.98 kcal/mol (Ki = 7.70 µM), with significant interactions with the THR-315 residue. In the case of Upc2, the binding energy was -7.15 kcal/mol (Ki = 5.73 µM), with hydrogen bond formation with TYR-724. These results suggest that Turmerone has the potential to inhibit critical enzymes involved in fungal metabolism, positioning it as a promising candidate for antifungal therapy. However, further in vitro and in vivo studies are required to validate its efficacy and safety. This study provides valuable insight into Turmerone's antifungal potential and lays the foundation for future therapeutic development.